Studi Kasus Putusan Pengadilan Agama Demak Nomor 539/Pdt.G/2019/PA.Dmk Terhadap Pegawai Negeri Sipil (PNS) Wanita yang Menjadi Istri Kedua Ditinjau dari Peraturan Perundang-undangan Terkait - Nurul Maulidina Jamilah; Hazar Kusmayanti; Betty Rubiati (International Forum of Researchers and Lecturers, 2023)
Female civil servants are absolutely prohibited from becoming second/third/fourth wives as regulated in Government Regulation Number 45 of 1990 concerning Marriage and Divorce Permits for Civil Servants, with the threat of sanctions for those who violate. Problems occur if the judge grants the request for polygamy with the prospective second wife's position as a civil servant with one of the judge's considerations which is not in accordance with the Legislative Regulations, namely ordering the prospective second wife to attach a Certificate of Giving Permission from Her Superior, as in the Decision of the Demak Religious Court Number 539/Pdt. G/2019/PA.Dmk. This research aims to determine the validity of the Certificate of Giving Permission from the Superior submitted by the prospective second wife in the decision in terms of the relevant Legislation. The approach method used in this research is normative juridical with research specifications, namely analytical descriptive, meaning that the events being researched are described using primary, secondary and tertiary legal materials. This research uses qualitative juridical analysis methods to produce descriptive data. The results obtained from this research are that the validity of the Certificate of Granting Superior Permission submitted by the prospective second wife should not have perfect legal force and can be canceled because it does not comply with the provisions in Article 4 paragraph (2) of Government Regulation Number 45 of 1990 concerning Marriage Permits and Divorce for Civil Servants.